Development and characterization of low-friction coatings for protection against fretting wear in aerospace components - Korsunsky, A; Torosyan, A; Kim, K (2009)
The application of different deposition and characterization techniques for low-friction coatings for protection against fretting wear in aerospace components was studied. Mechano-chemical deposition technique is a new coating method that combines the characteristics of mechanochemistry (mechanical alloying) and shot peening. Results obtained from fretting wear tests on mechanochemically deposited coatings showed that the use of this deposition technique method for Mo + S and C-DLC coatings leads to the creation of well-adhered dry film lubricating layers on titanium alloy substrates, and bring about a significant improvement of tribological characteristics. A universal tension-compression servohydraulic testing machine with an indenter attachment in the form of razor-blade was used to evaluate the coating thickness of soft-coated systems in the course of the fretting wear process. The load-displacement evolution during indentation through the coating layer and the substrate showed significant differences with each other.